2022
DOI: 10.1101/2022.04.02.486808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain-heart interactions are optimized across the respiratory cycle via interoceptive attention

Abstract: Respiration and heartbeat continuously interact within the living organism at many different levels, representing two of the main oscillatory rhythms of the body and providing major sources of interoceptive information to the brain. Despite the modulatory effect of respiration on exteroception and cognition has been recently established in humans, its role in shaping interoceptive perception has been scarcely investigated so far.In two independent studies, we investigated the effect of spontaneous breathing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…With respect to tactile processing, Grund et al (2022) found that both cardiac and respiratory cycles modulated stimulus sensitivity, with hit rates being maximal at peak expiration and minimal at peak inspiration. With respect to interoception (i.e., the perception of internal, visceral sensations), Zaccaro et al (2022) investigated respiratory cycle effects on cardiac interoception and reported that heartbeat-evoked cortical potentials were maximal during exhalation versus inhalation. This was further coupled with higher heartbeat tapping accuracy, suggesting that interoceptive sensitivity may be greatest when diaphragmatic pressure increases in the chest during the respiratory baroreflex (Molle & Coste, 2022; Zaccaro et al, 2022).…”
Section: Breathing On the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to tactile processing, Grund et al (2022) found that both cardiac and respiratory cycles modulated stimulus sensitivity, with hit rates being maximal at peak expiration and minimal at peak inspiration. With respect to interoception (i.e., the perception of internal, visceral sensations), Zaccaro et al (2022) investigated respiratory cycle effects on cardiac interoception and reported that heartbeat-evoked cortical potentials were maximal during exhalation versus inhalation. This was further coupled with higher heartbeat tapping accuracy, suggesting that interoceptive sensitivity may be greatest when diaphragmatic pressure increases in the chest during the respiratory baroreflex (Molle & Coste, 2022; Zaccaro et al, 2022).…”
Section: Breathing On the Brainmentioning
confidence: 99%
“…With respect to interoception (i.e., the perception of internal, visceral sensations), Zaccaro et al (2022) investigated respiratory cycle effects on cardiac interoception and reported that heartbeat-evoked cortical potentials were maximal during exhalation versus inhalation. This was further coupled with higher heartbeat tapping accuracy, suggesting that interoceptive sensitivity may be greatest when diaphragmatic pressure increases in the chest during the respiratory baroreflex (Molle & Coste, 2022; Zaccaro et al, 2022). Finally, with respect to self-related processing, a study reported the existence of an “embreathment illusion” such that projecting respiratory rhythms onto a virtual avatar increased feelings of bodily awareness and immersion (Monti et al, 2020).…”
Section: Breathing On the Brainmentioning
confidence: 99%